2018
DOI: 10.4178/epih.e2018050
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a sunlight exposure questionnaire for urban adult Filipinos

Abstract: OBJECTIVESTo develop and validate a self-reported sunlight exposure questionnaire (SEQ) for urban adult Filipinos.METHODSThe study included adults (19-76 years old) in Metro Manila, Philippines, well-versed in the Filipino (Tagalog) language and had resided in Metro Manila for at least 1 year. Exclusion criteria included pregnancy, active skin disorders, and immunocompromised states. An expert panel created a questionnaire in Likert-scale format based on a conceptual framework and 4 existing instruments. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 13 publications
(24 reference statements)
0
14
0
Order By: Relevance
“…Further south, the Philippines (13°N) is a more distinct potential outlier though again total numbers are quite small but indicate higher fatality rates for hospitalised cases. The Philippines has noted serious concerns about vitamin D levels after a small study found that 58% (214/369) of randomly tested office workers in Manila were deficient [41]. Phillipine Dr Mark Alipio recently published a (preprint) retrospective multicentre study of 212 cases with laboratory-confirmed infection of SARS-CoV-2 from three hospitals in Southern Asian countries.…”
Section: Discussionmentioning
confidence: 99%
“…Further south, the Philippines (13°N) is a more distinct potential outlier though again total numbers are quite small but indicate higher fatality rates for hospitalised cases. The Philippines has noted serious concerns about vitamin D levels after a small study found that 58% (214/369) of randomly tested office workers in Manila were deficient [41]. Phillipine Dr Mark Alipio recently published a (preprint) retrospective multicentre study of 212 cases with laboratory-confirmed infection of SARS-CoV-2 from three hospitals in Southern Asian countries.…”
Section: Discussionmentioning
confidence: 99%
“…Domains identified using exploratory factor analysis, as seen in Table 1 , were intensity of sunlight exposure (items 1–7), factors affecting sunlight exposure (items 8–19), and sun protection practices (items 20–25), which had satisfactory internal consistency generally and independently (Cronbach alpha > 0.7). Good test-retest reliability was established when all 260 adult participants completed the first and second testing with no significant differences from their responses 2 weeks apart [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is quintessential that the newly developed Filipino SEQ be evaluated for clinical use. This study aims to determine the association of different levels of sunlight exposure, measured using the SEQ locally developed by Yu et al [ 8 ], with 25-OHD levels among working urban adult Filipinos.…”
Section: Introductionmentioning
confidence: 99%
“…The one-week SES was adopted to provide participants with an accurate recall and account of sun exposure behavior. However, some studies have examined longer periods, ranging from a few weeks to several years, allowing a more reliable estimate of sun exposure for people who rarely expose themselves [ 63 , 71 , 76 , 77 , 89 ]. Furthermore, the SES was administered only once since exposure behavior constantly changes depending on heat preferences, sun protection measures [ 90 ], individual needs, and habits.…”
Section: Discussionmentioning
confidence: 99%
“…We developed a scale to estimate women’s sun exposure by considering all factors related to sun exposure that affect vitamin D levels, including phototype, weather, time and frequency of sun exposure, body parts exposed, and different sun protection behaviors. This score was developed from an extensive literature review of questionnaires assessing sun exposure in correlation or not with vitamin D levels [ 63 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ]. A unique feature of our questionnaire is the inclusion of indoor exposure as a significant determinant of sun exposure, considering the specificity of Moroccan culture and home architecture that favor adequate indoor sun exposure.…”
Section: Methodsmentioning
confidence: 99%